New species of zerconid mites from southern Europe and the Macaronesian region (Acari: Mesostigmata: Zerconidae) - Moraza, María Lourdes (Zootaxa, 2006)
Two new species of Prozercon and three new species of Zercon (Acari: Zerconidae) are described and illustrated on the basis of material collected from different habitats (natural, reforested and felled habitats) in Navarra (northern Spain) and Tenerife (Canary Islands).